Parenting Module Development Based on Intelligences Intelektual, Emotional, and Spiritual (IES) for Strengthening Student Character in Boarding Schools - Moh. Yusuf; Thamrin Tahir; Abdul Saman (LPPM STIE KRAKATAU, 2024)
Purpose: This study aimed to describe the level of need, determine the design form, and analyze the level of validation, practicality, and effectiveness of developing IES-based parenting modules in strengthening the character of students in boarding schools. Methodology: Research using Research and Development (R&D) with the ADDIE model approach (Analysis, Design, Development, Implementation and Evaluation) with data and information collection techniques carried out through documentation studies, literature studies, filling out questionnaires, interviews, and digging primary sources of information relating to the upbringing of students in dormitories, which can be accounted for. Results: The results of this research were qualitative and quantitative. The results showed that (1) the development of this IES-based parenting module is based on the needs of boarding teachers and students; and (2) the module design follows the structure of the learning model, which consists of a cover page, an introduction containing rationale, aims, benefits, targets, foundations,principles of care, models of care, main duties of boarding teachers, stages of care, daily life of students, and operational standards for boarding teachers. (3) The module developed is proven to be valid based on the validator's assessment, receiving an average score of 4.55, which means Very Good. (4) the assessment of the practicality of the module obtained an average of 4.33 on the effective usefulness of the module in helping the implementation of care, and 4.24 on the ease of the module to understand and carry out, and at 4.29 on the evaluation of questions that are appropriate to the care material being taught. (5) In the effective assessment, it can be concluded that care using the IES-based care module is effective, based on a student completion of 87.09%. This research adds to the scientific knowledge and helps in the form of parenting modules for schools, boarding teachers, and students.